2018
DOI: 10.1016/j.jvs.2018.05.224
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial evaluating negative pressure therapy to decrease vascular groin incision complications

Abstract: This study suggests that negative pressure therapy significantly reduces the major wound complication, reoperation, and readmission rates for patients at high risk for groin wound complications. Furthermore, this therapy may lead to a reduction in hospital costs. Negative pressure therapy for all groin incisions considered at high risk for wound complications is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
136
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(141 citation statements)
references
References 41 publications
5
136
0
Order By: Relevance
“…All the included studies reported a reduced incidence of SSIs in the NPWT group compared with the standard dressing group. The results were significant in three studies. Meta‐analysis of the seven studies, including all incisions from all arterial procedures, showed a reduction of SSIs, with an OR of 0·35 (95 per cent c.i.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…All the included studies reported a reduced incidence of SSIs in the NPWT group compared with the standard dressing group. The results were significant in three studies. Meta‐analysis of the seven studies, including all incisions from all arterial procedures, showed a reduction of SSIs, with an OR of 0·35 (95 per cent c.i.…”
Section: Resultsmentioning
confidence: 92%
“…). Of these, seven studies (from 13 records) were considered to have met the inclusion criteria: Kwon et al ,. Gombert et al ,.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations